Chronic Pelvic Pain after Laser Prostatectomy: Treatment by Resection of the Perineal Branches of the Pudendal Nerve - Dellon, A. Lee; Wright, E. James; Manson, Paul N. (Journal of Reconstructive Microsurgery, 2014)
Development of chronic pelvic pain after laser resection for benign prostatic hypertrophy has not been described previously (Clavien IIIb complication). The etiology of this chronic pain, which persisted despite medical chronic pain and urologic management for 5 years, was proven to be of pudendal nerve origin by local anesthetic blockade of the pudendal nerves bilaterally at the ischial spines. Surgical treatment was based upon the anatomic proximity of the perineal and dorsal branches of the pudendal nerve to the site of laser therapy on the pelvic side of the urogenital diaphragm. Treatment required resection of the perineal branches of the pudendal nerve bilaterally and neurolysis of the dorsal nerve to the penis bilaterally through incisions overlying the inferior pubic ramus. Relief of perineal pain and pain with micturition occurred in the immediate postoperative period. Pain relief and resumption of all normal activity occurred by 3 months postoperatively and continues 13 months following the surgery.
Keywords: prostatectomy; pudendal nerve; laser